Successful Pregnancy in a Female with a Large Prolactinoma after Pituitary Tumor Apoplexy. (30th September 2013) - Al-Sharafi, Butheinah A.; Nassar, Omar H.
Abstract : Pituitary apoplexy is a rare condition which may cause death of the patient in severe cases and many times leads to hypopituitarism. We report a case of apoplexy in a large prolactinoma resulting in empty sella syndrome followed by a successful pregnancy. Our patient is a 32-year-old female with a history of a macroprolactinoma for approximately 17 years who presented to our hospital with a history of severe headache, decreased level of consciousness, fever, nausea, vomiting, and diplopia of 12 hours duration. Magnetic resonance imaging done on admission showed an increase in the size of the pituitary adenoma with a subtle hemorrhage. The patient was admitted to the intensive care unit and treated conservatively. The condition of the patient improved within a few days. A few months later, she started having regular menstrual periods. A magnetic resonance imaging of the pituitary 1.5 years later was reported as empty sella syndrome, and approximately one year later she became pregnant. With the pituitary adenoma being resolved after developing pituitary apoplexy and continuing on cabergoline, the patient had a successful pregnancy with no recurrence of the adenoma after delivery and breastfeeding.